Interventions Used in the Psychotherapeutic Treatment of Post-Traumatic Stress Disorder (PTSD) - Carneiro, Juliana Margarida; Bertelli, Rosangela (Advances in Social Sciences Research Journal, 2021)
Post-traumatic stress disorder (PTSD), a highly prevalent psychopathological condition, results from exposure to a traumatic event that evokes fear, helplessness and horror. However, effective psychotherapeutic interventions have been developed that allow for the relief of symptoms and improvements associated with the functioning of patients diagnosed with this condition. The purpose of this review of clinical reports, published between 2014 and 2019 in journals indexed in the Online Library of Knowledge (B-on), was to provide an overview of the interventions that were used, by psychologists or other health professionals, in the psychotherapeutic treatment of the aforementioned disorder. Fifty one publications that met the inclusion criteria were identified and there was a predominance of the cognitive-behavioural approach, with strategies and procedures derived from the Cognitive-Behavioural Model of Learning. The results were later discussed.